2014
DOI: 10.1002/2014wr015567
|View full text |Cite
|
Sign up to set email alerts
|

A hiddenMarkov model combined with climate indices for multidecadal streamflow simulation

Abstract: Hydroclimate time series often exhibit very low year-to-year autocorrelation while showing prolonged wet and dry epochs reminiscent of regime-shifting behavior. Traditional stochastic time series models cannot capture the regime-shifting features thereby misrepresenting the risk of prolonged wet and dry periods, consequently impacting management and planning efforts. Upper Colorado River Basin (UCRB) annual flow series highlights this clearly. To address this, a simulation framework is developed using a hidden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…With a regime‐shifting model, the distribution of an observable hydrological variable (e.g., streamflow) shifts in concert with an unobserved (or “hidden”) regime state variable. The latter is assumed to be a discrete, stochastic process, such as a Markov chain, that tends to transition on an interannual basis [ Thyer and Kuczera , ; Sveinsson et al ., ; Akintug and Rasmussen , ; Prairie et al ., ; Gelati et al ., ; Bracken et al ., ]. The regime‐shifting model offers several desirable features, including compatibility with actual climate drivers that fluctuate inter‐annually, accurate reflection of the lack of knowledge of the factors that underpin observed hydrology, and compatibility with the useful and theoretically defensible assumption of stationarity [ Koutsoyiannis and Montanari , ; Serinaldi and Kilsby , ].…”
Section: Introductionmentioning
confidence: 99%
“…With a regime‐shifting model, the distribution of an observable hydrological variable (e.g., streamflow) shifts in concert with an unobserved (or “hidden”) regime state variable. The latter is assumed to be a discrete, stochastic process, such as a Markov chain, that tends to transition on an interannual basis [ Thyer and Kuczera , ; Sveinsson et al ., ; Akintug and Rasmussen , ; Prairie et al ., ; Gelati et al ., ; Bracken et al ., ]. The regime‐shifting model offers several desirable features, including compatibility with actual climate drivers that fluctuate inter‐annually, accurate reflection of the lack of knowledge of the factors that underpin observed hydrology, and compatibility with the useful and theoretically defensible assumption of stationarity [ Koutsoyiannis and Montanari , ; Serinaldi and Kilsby , ].…”
Section: Introductionmentioning
confidence: 99%
“…The HMM uses Markov chain assumption, in which the probability of the occurrence of next state depends only on the current state and not on the rainfall state that preceded it in the state space (Zucchini and Guttorp, ). In sum, the HMM accounts for spatial dependence in the data and capture the spatio‐temporal pattern of rainfall intensity and its probability of occurrence over a network of stations or grid points (Robertson et al, ; Greene et al, ; Bracken et al, ; Pal et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The HMM uses Markov chain assumption, in which the probability of the occurrence of next state depends only on the current state and not on the rainfall state that preceded it in the state space (Zucchini and Guttorp, 1991). In sum, the HMM accounts for spatial dependence in the data and capture the spatio-temporal pattern of rainfall intensity and its probability of occurrence over a network of stations or grid points (Robertson et al, 2006;Greene et al, 2008;Bracken et al, 2014;Pal et al, 2015). The HMM tool developed by the International Research Institute (IRI) was employed in this study to identify rainfall states that could capture the spatio-temporal variability within the NEIMR season over the study region (IRI, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…[] and Bracken et al . []. Lower Colorado Basin flows are also modulated by these climate forcings [ Thomas , ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently , Bracken et al . [] showed that regime‐like behavior of the Colorado River flows are forced by AMO and PDO, and used a nonhomogeneous hidden Markov model to simulate the flow properties using these two climate forcings.…”
Section: Introductionmentioning
confidence: 99%